PEMANFAATAN SMART APPS CREATOR (SAC) SEBAGAI SOFTWARE DALAM MEMBUAT APLIKASI MEDIA PEMBELAJARAN MUSIK - Hamid, Nuryati Hasni; Andriyanto, R.M. Aditya; Adi, Tuti Tarwiyah (Jurnal Penelitian Musik, 2021)
The aim of this study is to determine the use of Smart Apps Creator (SAC) as a device that can create interactive learning media applications to be used as an alternative online learning media at SMA Negeri 9 Jakarta. The research method used to collect research data is a qualitative research method with a descriptive approach, including observation, documentation, interviews and literature studies. The research results obtained are Smart Apps Creator (SAC) can create interactive learning media applications for students. The application makes it easier for students in the learning process, especially in music material. The material in the application can be accessed offline, designed with a game pattern model to make the student learning process comfortable and Happy.